The Harmonic Mind Map in the Comprehension of Narrative Texts in University Students - Novoa Castillo, Pedro Félix (2018)
This article deals with the effect of the Harmonic Mind Maps (HMM) in the comprehension of narrative texts of university students. To achieve this purpose, a quasi-experimental research was carried out within the quantitative approach. From a population of 1500 students belonging to the I Semester of university, a sample of 83 students was taken, and they were divided into two groups: one of control (43) and the other one experimental (40). For the collection of data, adaptations of the PISA Test, 2015 were used. After the application of the HMM, it is concluded that its use positively influences the comprehension of narrative texts.